Guanine Metal Complexes: Spectroscopic Studies, Dying Performance and as Indicator - Edrees, Asmaa; Alyaa Khider Abbas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Azo dyes are the most common and widely used dyes, accounting for more than half of each year’s dyes. In this work, a complete description of a new innovative series of compounds with the elements [Ag (I), Zn (II)] generated from the guanine azo dye ligand (GAB) 8-[1-(3-carboxy) azo] guanine has been studied. The structural formula was studied using several physicochemical analyses and spectroscopic techniques (FT-IR spectra, UV-Vis). The FTIR spectrum of the ligand (GAB) was compared to the spectra of the metal ion complexes formed to determine its identity. Chelating caused some changes in the spectra of the complexes to appear to demonstrate that they could be linked to the ligand. The complexes have a tetrahedral geometry shape, the ligand functions as a bidentate ligand, and thermogravimetric analysis (TGA) is used to measure the thermal stability of compounds. The findings and equation presented by the analytical data seemed to be in good accord with the conclusions of the thermogravimetric investigation, which demonstrated that the disintegration of the ligand (GAB) and its complexes occur in multiple steps. The configuration that follows weakens thermal stability: GAB(35.52%)>[Ag(GAB)(H2O)2]NO3.2H2O(34.6%)>[Zn(GAB)Cl2].H2O(31.54%), and the complexes have tetrahedral geometry shape. Furthermore, elemental analysis, mole ratio, and the mole ratio of each complex (1:1) (M:L). The ligand was effective as an acid-base indicator when the pH changed; they exhibited a striking color change, similar to how the ligand (GAB) and its complexes can be used to dye wool textiles due to their wide range of colors. It investigated how well the ligand (GAB) and its complex worked as a wool dye. The ligand GAB and its metal complexes were used to color most of the protein filaments in wool fiber, which have a complex structure with amino and carboxyl groups and colors ranging from orange to green.